The Fate of Jakarta Special Autonomy After The Movement of The Capital City of The United State of The Republic of Indonesia - Yulizar Pramudika Tawil; Syugiarto; Giska Mala Rahmarini (Journal of Public Administration and Government, 2022)
The purpose of this research is to determine if Jakarta retains unique autonomy if the capital city is relocated to East Kalimantan. Furthermore, this article analyses various nations that have relocated their capital cities and compares them to Indonesia, which is now considering to relocate its capital city. The case study technique was employed in this investigation. The results of this article suggest that Indonesia can choose one of three strategies (1. Moving the Capital City, Government Center, and Business Center; 2. Moving just the Capital City and Government Center; or 3. Moving only the Government Center), with the impact of picking one of these schemes being: 1) If the capital is relocated, Jakarta would lose its unique autonomy as a special capital city; 2) If laws are implemented as a special commercial region or trade hub in Indonesia, Jakarta will still have special autonomy; 3). If just the center of the Indonesian government is relocated to East Kalimantan, Jakarta will retain special autonomy as a special capital region.